2019
DOI: 10.1016/j.bpj.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Ion Condensation onto Ribozyme Is Site Specific and Fold Dependent

Abstract: The highly charged RNA molecules, with each phosphate carrying a single negative charge, cannot fold into well-defined architectures with tertiary interactions, in the absence of ions. For ribozymes, divalent cations are known to be more efficient than monovalent ions in driving them to a compact state although Mg 2+ ions are needed for catalytic activities. Therefore, how ions interact with RNA is relevant in understanding RNA folding. It is often thought that most of the ions are territorially and non-specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 31 publications
11
63
0
Order By: Relevance
“…Accurate simulations using coarse-grained models of ribozymes in explicit monovalent and divalent cations 85 is computationally demanding. 25,26 In order to simplify the problem, while still retaining a high level of accuracy in predicting the RNA folding thermodynamics and kinetics, we developed a theory to treat the electrostatic interactions involving monovalent ions implicitly, while treating the many body effects due to divalent ions explicitly. 38 Briefly, we assumed that the screening effect due to monovalent cations, especially when present at high concentrations, can be described by the classical Debye-Huckel (DH) theory.…”
Section: Divalent Ion-phosphate Interactionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accurate simulations using coarse-grained models of ribozymes in explicit monovalent and divalent cations 85 is computationally demanding. 25,26 In order to simplify the problem, while still retaining a high level of accuracy in predicting the RNA folding thermodynamics and kinetics, we developed a theory to treat the electrostatic interactions involving monovalent ions implicitly, while treating the many body effects due to divalent ions explicitly. 38 Briefly, we assumed that the screening effect due to monovalent cations, especially when present at high concentrations, can be described by the classical Debye-Huckel (DH) theory.…”
Section: Divalent Ion-phosphate Interactionmentioning
confidence: 99%
“…2,25 40 Recently, simulations of a large ribozyme and several other RNA constructs, in the presence of both monovalent and divalent ions, have shown that the ions have a strong propensity to bind to nucleotides in a site-specific manner, and not uniformly. [25][26][27] The irregular shape of the RNA plays an important role in determining where the ions bind, as the ions are naturally drawn to the highly negatively charged pockets.Other studies, focusing only on the folded states or well-defined complexes involving RNA, have shown 45 that the site-specifically bound Mg 2+ ions to various RNA molecules are stable. [28][29][30][31][32][33] These studies did not consider ion-driven folding of RNA from a completely unfolded state, which is the subject of our interest here and elsewhere.…”
mentioning
confidence: 99%
See 3 more Smart Citations